Selenium improves the flavor-promoting substances of summer tea (Camellia sinensis) by altering the expression of flavonoid and amino acids metabolic genes - Ruiming Zhang; Huishan Tang; Xinlong Hu; Yuqiong Chen; Dejiang Ni; Mingle Wang (Horticulture Advances)
Abstract Summer tea (Camellia sinensis) is less favored due to its inferior taste compared to spring tea. The application of selenium (Se) has proven effective in enhancing tea flavor. However, the specific mechanisms underlying the Se-mediated improvement of summer tea quality remain unclear. This study examines the alteration of trace elements, the metabolome, and the transcriptome in tea plants subjected to Se treatment. Se application increased the concentrations of B, Fe, Zn, and Se in the summer tea shoots of certain cultivars. Metabolomic analysis revealed that exogenous Se elevated the levels of theanine and flavonoids while reducing the catechin bitterness taste index in most of the selected cultivars. Transcriptomic analysis further demonstrated that Se treatment modulated the expression of CsSULTRs, CsPHTs, CsIRTs, CsZIPs, and CsBOTs, indicating a potential link between the accumulation of these elements and the corresponding transporter genes. Based on qRT-PCR results, CsSULTR1.1, 1.2, and 4.1 are likely involved in Se transport. Additionally, differentially expressed genes (DEGs) were predominantly enriched in the flavonoid and amino acid biosynthesis pathways following Se treatment. In conclusion, the addition of Se enhances the flavor profile of summer tea by modulating genes participating in flavonoid and amino acid metabolism, underpinning its potential for improving summer tea quality.